217k views
3 votes
4x + 6 = 2(2x +3) is an example of what type of equation?

1 Answer

2 votes

Answer:

Simplifying

4x + -6 = 2(2x + 3)

Reorder the terms:

-6 + 4x = 2(2x + 3)

Reorder the terms:

-6 + 4x = 2(3 + 2x)

-6 + 4x = (3 * 2 + 2x * 2)

-6 + 4x = (6 + 4x)

Add '-4x' to each side of the equation.

-6 + 4x + -4x = 6 + 4x + -4x

Combine like terms: 4x + -4x = 0

-6 + 0 = 6 + 4x + -4x

-6 = 6 + 4x + -4x

Combine like terms: 4x + -4x = 0

-6 = 6 + 0

-6 = 6

Solving

-6 = 6

User Somerandomusername
by
5.0k points